HIV risk perception, trust and PrEP adherence among participants in an HIV prevention trial: a qualitative longitudinal study, South Africa - Giuseppe Pantaleo; Glenda Gray; Pontiano Kaleebu; Said Aboud; David Dunn; Merlin Robb; Janet Seeley; Sheena McCormack; Julie Fox; Jim Rooney; Tom Miller; Agricola Joachim; et al. (BMJ Open)
Introduction Ensuring the effectiveness of HIV prevention and treatment methods requires high levels of adherence. Studies have recognised the significance of trust in shaping HIV risk perception.Aim In this qualitative analysis, our aim was to explore risk perceptions and understand how individuals assess and respond to HIV risks, as well as their uptake and adherence to oral pre-exposure prophylaxis (PrEP).Setting The study was based on the setting of an HIV prevention trial conducted in South Africa.Methods Thirty individuals, 9% of the total clinical trial participants, enrolled in the clinical trial were purposively selected and interviewed at three time points within the trial during the follow-up phase. Data analysis was conducted using the Trust, Confidence and Cooperation framework that included constructs of trust, confidence and cooperation.Results The findings show that the ongoing participation in the clinical trial played a significant role in influencing participants’ decision to continue PrEP as HIV prevention. This decision was grounded in their trust that PrEP would effectively reduce their vulnerability to HIV and infection.Conclusion Clear and consistent health-promoting initiatives enhance participants’ self-awareness of HIV risks and promote understanding (uptake) and effectiveness of HIV prevention methods.Trial registration number NCT04066881.